Systematic Literature Review: Scope Analysis of Research on Mathematics Learning Media - Anthony Saputra; Anggun Badu Kusuma (UMSU, 2023)
Good learning media is learning media that is able to provide stimulation to students so as to generate interest in learning. Various types of media, of course students have no difficulty in choosing what media to use, both audio-based, visual-based, and audio-visual-based media. Learning media can be used to generate student learning motivation so that it can improve students' problem-solving abilities. This study aims to conduct a literature review related to effectiveness in learning mathematics at all levels. The research method chosen in this study is SLR (Systematic Literature Review). Data collection was carried out by documenting all articles that had similar research within the last 10 years in this research report. The articles used were 15 national journal articles accredited by Sinta obtained from Google Schoolar. Based on this research, it was found that the use of mathematics learning media can improve students' problem solving abilities, change the mindset and creativity of learning to be more fun. Based on the literature review conducted, learning media can be developed at all levels.